Candida in saliva of Brazilian hemophilic patients Candida na saliva de pacientes hemofílicos brasileiros - Claudio Maranhão Pereira; Fábio Ramôa Pires; Maria Elvira Pizzigatti Corrêa; Osvaldo di Hipólito Júnior; Oslei Paes de Almeida (University of São Paulo, 2004)
Hemophilia is a common hereditary hemorrhagic disorder, however little is known about the oral microflora of hemophilic patients. The aim of this study was to quantify the Candida and identify its species in non-stimulated saliva of hemophilic patients, and consider its relationship with clinical factors influencing Candida carriage. This study comprised evaluation of 86 hemophilic patients of the Hematology Center/UNICAMP and 43 healthy subjects as controls. All patients were submitted to anamnesis, intraoral examination and unstimulated saliva collection. Candida counts and species identification were performed in salivary samples. Candida was present in 64% of the hemophilic patients and in 44% of the healthy controls. C. albicans represented 65% and 68% of the isolated species, in hemophiliacs and control group respectively, and C. tropicalis was the second most common species in both groups. These results indicate that hemophilic patients carry Candida more frequently and in higher counts than healthy controls, independently of oral clinical parameter considered, as viral infections, complete dentures, transfusions of hemoderivatives, and salivary flow. Hemofilia é uma alteração hemorrágica hereditária comum, entretanto pouco se sabe a respeito da microbiota oral destes indivíduos. O objetivo deste estudo foi quantificar a presença de Candida e identificar as suas espécies na saliva de hemofílicos, correlacionando os resultados com fatores clínicos que possam influenciar a presença deste fungo. Foram avaliados 86 hemofílicos do Hemocentro/UNICAMP e 43 indivíduos saudáveis. Todos os pacientes foram submetidos a anamnese, exame clínico intra-oral e coleta de saliva de forma não estimulada. A quantificação e identificação das espécies de Candida foram realizadas nas amostras de saliva. Candida estava presente em 64% dos hemofílicos e em 44% dos indivíduos saudáveis. C. albicans representou 65% e 68% das espécies identificadas, nos hemofílicos e grupo controle respectivamente, e C. tropicalis foi a segunda espécie mais comum. Estes resultados sugerem que pacientes hemofílicos albergam mais freqüentemente Candida na cavidade bucal e em maiores quantidades que os indivíduos do grupo controle, independentemente dos parâmetros clínicos analisados, como infecção viral, próteses dentárias, transfusões de hemoderivados e fluxo salivar.